South America 2025 - Albiston, Isabel; Bianchi, Barbara; Egerton, Alex; Freeman, Bailey; Gill, Victoria; Ham, Anthony; Holden, Trent; Johanson, Mark (Travel writer); Sainsbury, Brendan; Sharples, Carinya; Smith, Paul, 1976 December 18-; Yanagihara, Wendy (Lonely Planet guidebooks., 2025)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime in this latest edition of our guide to South America. Discover South America's most popular experiences and best kept secrets from admiring one of Argentina's greatest natural wonders, the majestic Glaciar Perito Moreno; to taking in Patagonia's dramatic scenery on a road trip along Chile's Carretera Austral; and marvelling at the striking stone ruins of Ingapirca, Ecuador's most important archaeological site.